Walking is a Feasible Physical Activity for People with Rheumatoid Arthritis: A Feasibility Randomized Controlled Trial. (31st July 2015) - Baxter, Susan V.; Hale, Leigh A.; Stebbings, Simon; Gray, Andrew R.; Smith, Catherine M.; Treharne, Gareth J.
Abstract: Background: Exercise has been recognized as important in the management of rheumatoid arthritis (RA). Walking is a low‐cost and low‐impact activity, requiring little supervision. It requires no specialist training, is suited to a variety of environments and is inherently a clinically meaningful measure of independence. The aim of the present study was to determine whether a designed walking programme for people with RA successfully facilitated regular physical activity in participants, without detriment to pain levels. Methods: Thirty‐three people with RA were recruited from Dunedin Hospital rheumatology outpatient clinics and enrolled in a walking randomized controlled trial (RCT) feasibility study. Participants were randomly allocated to the walking intervention ( n = 11) or control ( n = 22) groups. Control participants received a nutrition education session, and the walking intervention group received instructions on a walking route with three loops, to be completed 3–4 times per week. The walking route shape was designed so that the length of the walk could be tailored by participants. Both groups were assessed at baseline and six weeks later. The primary outcome measures were feasibility, acceptability and safety. The principal secondary outcome was change in walking speed after the intervention. Additional outcome measures were a step‐up test, activity limitations (on the Health Assessment Questionnaire), global well‐being (on the European Quality of Life Questionnaire), self‐efficacy for managing arthritis symptoms, self‐efficacy for physical activity, daily pedometer readings and a daily visual analogue scale for pain. Results: Participants successfully completed the walk for the suggested frequency, indicating feasibility and acceptability. There were no reported adverse effects of participation and the walking intervention group did not have higher daily pain levels than the control group, indicating safety. The walking intervention group showed a pattern of improvements in self‐efficacy and global well‐being; no changes in these outcomes were noted in the control group. No outcome measure showed statistically significant between‐group differences. Conclusions: Walking appears to be a feasible, acceptable and safe intervention for people with RA. These findings inform the design and power requirements of larger trials of structured walking interventions. Copyright © 2015 John Wiley & Sons, Ltd.